Parental-to-Embryo Switch of Chromosome Organization in Early Embryogenesis. Issue 7 (July 2020) - Collombet, Samuel; Ranisavljevic, Noémie; Nagano, Takashi; Varnai, Csilla; Shisode, Tarak; Leung, Wing; Piolot, Tristan; Galupa, Rafael; Borensztein, Maud; Servant, Nicolas; Fraser, Peter; Ancelin, Katia; et al.
Abstract : (Abstracted from Nature 2020;580:142–146) Paternal and maternal epigenome analysis has shown atypical patterns of histone modification in oocytes, sperm, and preimplantation embryos that undergo marked changes after fertilization. Previous studies have led to inconclusive evidence on the dynamics of local topological-associated domains (TADs) regarding their absence in the oocyte and appearance in the embryo versus preexistence in the zygote.